Wealth-to-income ratio and stock returns : evidence from the Euro Area - Sousa, Ricardo M. (2012)
I find that when the ratio of asset wealth to human wealth falls, investors become more exposed to labour income shocks and demand a higher risk premium for stocks. I show that the residuals of the trend relationship among wealth and labour income, wy, predict future stock returns in the Euro Area. The results are robust to additional control variables and show the superiority of wy vis-a-vis other benchmark models.